Physical, Thermal and Morphology Properties af Polyvinyl Alcohol-Based Composite Enhanced with Collagen and Bromelain for Cartilage Application - Nur Syafiqa Amirah Izam,; Hasraf, Nadirul; Hamzah, Syahir (Progress in Engineering Application and Technology, 2023)
This thesis reports the preparation of polyvinyl alcohol (PVA) film modified withcollagen and 3% bromelain via solvent casting and surface entrapment method forcartilage application. The concentration of collagen used was varied from 0 to 2% w/vthe hydrophilicity properties of the film was observed via swelling test and moistureabsorption test. PVA/2%Col with 3% bromelain having good swelling properties inphosphate buffer saline (PBS) solution and have a good results of moisture absorptioncompared to other films. PVA/2%Col with 3% bromelain concentration was chosen asthe optimum PVA/Collagen film and was further tested in order to observe its physicalproperties. The chemical interaction of the film was analyzed by Fourier TransfromInfrared Spectroscopy (FTIR). Scanning Electron Microscope (SEM) testing also havebeen conducted to observe it surface morphology. Differential Scanning Calorimetry(DSC) testing, PVA/2%Col with 3% bromelain film give a better results compared toother films. Futhermore, for In-vitro Biomineralization testing using SEM,PVA/2%Col with 3% bromelain shows good results. These report were clearlysuggestive that biopolymers such as PVA can exhibit an increasing of physicalproperties by treated with collagen and bromelain. This new modified towards thePVA film can enhance its quality and decrease the limitations of application in treatingcartilage application.